1996
DOI: 10.1063/1.869022
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear spatially developing Görtler vortices in curved wall jet flow

Abstract: Linear and nonlinear spatial developments of two-dimensional wall jets on curved surfaces are computed using pseudospectral-finite difference methods. Inviscid analysis shows that the instability originates from the inner/outer region on a concave/convex wall; the shear layer is thus always unstable regardless of the curvature. This primary instability is a steady spanwise vortex structure similar to Görtler instability in a Blasius flow. In the present study, a perturbation of prescribed wave number α is assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Wadey [15] used asymptotic methods for linear theory to study Görtler vortices in wall jet flows for large spanwise wavenumbers. It was found that curved wall jets on both concave and convex walls were more stable to streamwise vortices than boundary-layer flows.An experimental study of streamwise vortices appeared for wall jet flow on a concave wall, see Matsson [16], followed by nonlinear simulations of the same flow by Le Cunff and Zebib [17]. The simulations were able to capture the primary instability of streamwise vortices in the experiments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wadey [15] used asymptotic methods for linear theory to study Görtler vortices in wall jet flows for large spanwise wavenumbers. It was found that curved wall jets on both concave and convex walls were more stable to streamwise vortices than boundary-layer flows.An experimental study of streamwise vortices appeared for wall jet flow on a concave wall, see Matsson [16], followed by nonlinear simulations of the same flow by Le Cunff and Zebib [17]. The simulations were able to capture the primary instability of streamwise vortices in the experiments.…”
mentioning
confidence: 99%
“…An experimental study of streamwise vortices appeared for wall jet flow on a concave wall, see Matsson [16], followed by nonlinear simulations of the same flow by Le Cunff and Zebib [17]. The simulations were able to capture the primary instability of streamwise vortices in the experiments.…”
mentioning
confidence: 99%
“…The results are mathematically reliable only for ␣Ͼ0.1 since the matrices become ill-conditioned below this threshold. 18 The neutral curves are presented for decelerated and accelerated boundary layers in Fig. 4 on a convex wall where the curvature has a stabilizing effect.…”
Section: A Linear Resultsmentioning
confidence: 99%
“…4 Le Cunff and Zebib 18 verified the consistency of a u-normalization with a direct integration of the equation where no splitting is introduced.…”
Section: ͑24͒mentioning
confidence: 91%
See 1 more Smart Citation